A Boomerang, Porridge in the Pocket and Other Stories of "the Blacks' Camp". - Krichauff, Skye (Journal of Australian Studies, 2019)
Positive stories of 19th-century settler–Aboriginal interaction are not generally known or widely referred to by current generations of Australians. Focusing on stories of "the Blacks' camp" told by descendants of early South Australian settler George Cameron, and information about Aboriginal people published in local written histories, this article demonstrates how a settler-colonial historical epistemology frames and structures settler-descendants' historical consciousness. By excluding positive stories that contain the potential to disrupt common understandings regarding the outcome of colonisation, this epistemology hinders a deeper understanding of Australia's colonial past and, ultimately, postcolonial future.